Exploring the preferences for Chinese freehand painting among China retired elders by using nominal group technique (NGT) - Jiamei, Wu; ABD Shukor, Shureen Faris; Bin Hasna, Mohd Fabian; Daud, Mohd Najmi (Arts and Science Press Pte. Ltd., 2024)
The present study delves into the artistic preferences of retired seniors regarding Chinese freehand painting by applying the Nominal Group Technique (NGT). While Chinese freehand brush painting boasts a rich historical tradition, little is known about the specific tastes of retired seniors who possess ample free time and maintain strong cultural ties. Utilizing NGT, a systematic brainstorming process, the study engaged retired senior citizens residing in China to solicit their insights. The findings underscore a pronounced interest in the floral motifs in freehand-painted flower and bird scenes. Additionally, participants displayed a fondness for particular aspects of Chinese freehand paintings, characterized by the expression of intense emotions, subtle yet elegant color palettes, and a simple brushstroke technique. This study advocates for integrating traditional art in therapeutic settings to enrich the quality of life for seniors. It offers valuable insights into the artistic preferences of this specific demographic, shedding light on how art can resonate with their sensibilities.